The financialization of platform capital from the perspective of political economy - Hao Qi; Zhongjin Li; Yankai Wen (China Political Economy)
Purpose – The financialization of the platform economy is a crucial part of the theoretical landscape of the platform economy. However, it has not yet received adequate attention from the academic community. This deficiency has led to current research often neglecting the supportive role of finance capital in the platform economy, and consequently, there has been a lack of comprehensive interpretation of the generally poor profitability of platform companies. This paper aims to address the existing gap in the literature within this field. Design/methodology/approach – This paper examines the role of finance capital, particularly venture capital, in the platform economy and offers a political economy analysis of the historical background, accumulation logic, and inherent contradictions of the financialization of the platform economy. Findings – The paper argues that the advancement of new technologies, excess capital and labor supply in the post-crisis era, and the development of economic financialization, particularly the maturity and diffusion of the venture capital system, constitute the historical background of the financialization of the platform economy. Driven by finance capital, platform enterprises engage in excessive expansion to increase their financial valuations, forming a valuation-driven accumulation model. Financialization has caused the platform economy to deviate from its normal developmental trajectory. Platform enterprises exhibit higher shareholder payouts while simultaneously engaging in rapid investment expansion, leading to a trend of bubble-like development in the platform economy. Originality/value – The financialization of the platform economy has exacerbated the socio-economic problems caused by disembeddedness, deepening the contradiction between the speculative logic of finance capital and the healthy development of the real economy. This profoundly reflects the obstruction posed by contemporary capitalist relations of production to the development of productive forces. This paper provides several key policy insights for the formulation and implementation of relevant policies in China.